2022
DOI: 10.1002/er.7738
|View full text |Cite
|
Sign up to set email alerts
|

Surface functional group‐tailored B and N co‐doped carbon quantum dot anode for lithium‐ion batteries

Abstract: Summary Recently, carbon quantum dots (CQDs) have emerged as new surface modification agents for the anode materials of lithium‐ion batteries (LIBs) owing to their various advantages, including high surface area, low toxicity, low cost, and chemical stability. However, CQDs intrinsically possess large amounts of nonessential oxygen‐containing groups (CO and COH) at the surface, which can inhibit Li+ accessibility and lower electrical conductivity. Owing to these limitations, CQDs have been widely studied as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…In the XRD lines of the six samples, two broad steamed bread‐like diffraction peaks were observed at 24 and 44°. These two peaks correspond to the (002) and (100) planes of graphite, 31,32 indicating a disordered structure, which is highly consistent with the results of the HRTEM. At the same time, it is also observed that the intensity of the diffraction peak around 44° increases slightly with the heat treatment temperature, suggesting the higher temperature will lead to a higher degree of graphitization of the sample.…”
Section: Resultssupporting
confidence: 88%
“…In the XRD lines of the six samples, two broad steamed bread‐like diffraction peaks were observed at 24 and 44°. These two peaks correspond to the (002) and (100) planes of graphite, 31,32 indicating a disordered structure, which is highly consistent with the results of the HRTEM. At the same time, it is also observed that the intensity of the diffraction peak around 44° increases slightly with the heat treatment temperature, suggesting the higher temperature will lead to a higher degree of graphitization of the sample.…”
Section: Resultssupporting
confidence: 88%
“…First, the CQDs confers better Li ion transfer, charge carriers’ flux and, consequently, faster kinetics properties thanks to the presence of Nitrogen doping which generates additional active sites enhancing the overall lithiophilicity of the carbon‐based material. This positive effect has been also recently demonstrated in case of heteroatom (e. g., B, N or O)‐doped and/or co‐doped CQDs and other carbon materials (G, NG or GO) [40–42] . Additionally, the N‐doped CQDs can act on the solvation degree of Li + ions by inhibiting the formation of ion‐solvent (carbonates) clusters and promoting a better carrier migration [43] .…”
Section: Resultsmentioning
confidence: 56%
“…This positive effect has been also recently demonstrated in case of heteroatom (e. g., B, N or O)-doped and/or co-doped CQDs and other carbon materials (G, NG or GO). [40][41][42] Additionally, the N-doped CQDs can act on the solvation degree of Li + ions by inhibiting the formation of ion-solvent (carbonates) clusters and promoting a better carrier migration. [43] This results in improved cell rate performance and lifespan, as also found in case of polymer electrolytes gelled by LiPF 6 -based solutions.…”
Section: Electrochemical Performancementioning
confidence: 99%